Kesejahteraan Pendamping Program Keluarga Harapan (Studi Deskriptif Pendamping PKH di Jakarta Timur) - Dian Larasati; Fentiny Nugroho (Universitas Batanghari Jambi, 2023)
Poverty remains a global central issue in all countries in the world. The purpose of this research is to describe and analyze the welfare of PKH social workers in East Jakarta and the factors that support and hinder the welfare of PKH social workers in East Jakarta. This study uses a descriptive qualitative approach. The results of this study indicate that the welfare of PKH social assistants obtained so far includes subjective welfare and objective welfare. Subjective well-being includes feelings of well-being, satisfaction, that a person feels when working as a social companion. Meanwhile, objective welfare includes aspects of opinion that are felt to be sufficient to meet the daily needs of the companions, then expenditure aspects that are felt to be lower than income, housing that is available even if only by contact or renting, availability of health services even though the companions have to pay their own expenses. , transportation is smooth even though there are no additional costs for transportation. On the other hand, factors supporting the welfare of the companion of age, religious attitudes, social support from the community and village officials, personality of the companion, proper housing and good social conditions of the accompanying family. Meanwhile, the inhibiting factor is the companion's salary, which is still below the Jakarta’s UMP.